2014
DOI: 10.1093/jxb/eru130
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic flexibility in maize exposed to salinity and shade

Abstract: SummaryIn maize, salinity reduced photosynthesis by decreasing stomatal conductance. Shade downregulated PEPC more than Rubisco, leading to decreased bundle-sheath CO2 leakiness. The treatments elicited plasticity in NADP-ME/PEP-CK activity ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 62 publications
6
69
1
Order By: Relevance
“…Under nitrogen-rich conditions, N leaf is high and PEPC activity can increase to a greater extent than Rubisco, resulting in a high CO 2 concentration gradient between bundle sheath and mesophyll cells and then a high Ф value 15, 16 . However, different results were also reported in several studies 1719 and thus the relationship between N leaf and Ф might be species-specific. In terms of C i / C a , increasing N leaf improves the allotment of nitrogen to photosynthetic enzymes and further decreases the C i / C a through stimulating the photosynthetic capacity of the plant 20, 21 .…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Under nitrogen-rich conditions, N leaf is high and PEPC activity can increase to a greater extent than Rubisco, resulting in a high CO 2 concentration gradient between bundle sheath and mesophyll cells and then a high Ф value 15, 16 . However, different results were also reported in several studies 1719 and thus the relationship between N leaf and Ф might be species-specific. In terms of C i / C a , increasing N leaf improves the allotment of nitrogen to photosynthetic enzymes and further decreases the C i / C a through stimulating the photosynthetic capacity of the plant 20, 21 .…”
Section: Introductionmentioning
confidence: 65%
“…More and more studies in recent years reported that Ф can be changed by environmental conditions using online measurment or model methods. For instance, high vapour pressure deficit increased Ф 32 ; shade reduced Ф 19 . It was demonstrated that the balance of C3 cycle and C4 cycle could be changed by those environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Total PEPC activities in leaf extracts were measured using an NADH-coupled assay as described previously (Ashton et al, 1990;Sharwood et al, 2014). Extraction was performed using the same buffer as described above.…”
Section: Pepc and Nadp-me Activitiesmentioning
confidence: 99%
“…and internal biotic (photosynthetic enzymes, genotype, molecular mechanism, etc.) factors (Kakani et al 2003, Arena et al 2011, Pengelly et al 2011, Benesova et al 2012, Sharwood et al 2014. The abiotic factors are the initial drivers in controlling maize photosynthetic process; water, sunlight and temperature are the three main abiotic factors.…”
mentioning
confidence: 99%
“…Lack of sunlight (solar radiation) usually causes photoinhibition (light-induced decline in photochemical activity) (Aro et al 1993, Terashima et al 1994, Sharwood et al 2014. It is reported that photosynthesis is significantly inhibited at both low and high temperatures, which usually resulted in an impaired photosynthetic apparatus and a depressed photosynthetic capacity (Janda et al 1998, Crafts-Brandner and Salvucci 2002, Naidu and Long 2004, Ben-Asher et al 2008, Suwa et al 2010.…”
mentioning
confidence: 99%